Propuesta de plan para la implementación de producción más limpia en el proceso de refinación de aceite de Palma Africana y la elaboración de diversos productos derivados, caso de estudio Oliojoya Cía. Ltda - Vernaza Quiñónez, Lucía (2012)
The methodology of P + L is an indispensable tool in industries that wish to improve procedures and optimize production processes, for this reason the proposal of a CP plan was elaborated in Oliojoya Industria Aceitera Cía. Ltda. That seeks improvement in its processes in order to save resources, take care of the environment, increase its efficiency, and thereby generate profits for the company. The main objective of this proposal is the future application of the P + L methodology in Oliojoya Industria Aceitera Cía. Ltda. In the African palm oil refining production processes and the elaboration of various derivative products.